THE EFFECT OF DISTRIBUTION CHANNEL SALES VOLUME IN PT.VARIA INDAH PARAMITHA MANADO - Wolok, Revino E.; Mandey, Silvya L.; Kojo, Christoffel (Universitas Sam Ratulangi, 2015)
A company is successful in sales if the company is able to market their goods widely with a maximum benefit. In general, the bottleneck in distributing goods and services will cause a lot of trouble to both the consumer and the producer. Difficulties that will occur in the manufacturers include disruption of sales receipts resulting in the target scot miss macth. This will cause a flow of income needed by the company to perform continuity canâ€™t be expected.This study aimed to determine the effect of distribution channel to sales volume in PT.Varia Indah Paramitha Manado. The method used is associative.The population of this research is the average number of sales per month for five year . The sample used in turnover volume growth and cost disribution channel company for five years, with a purposive sampling technique. Results of analysis partially variable distribution channels Â positive and significant impact on sales volume. For the management of PT. Varia Indah Paramitha, must improve marketing through distribution channels marketing in order to increase the company's sales volume. Keywords : distribution channels, sales volume